Menstimulasi sikap kerukunan dalam jemaat: Sebuah model moderasi beragama menurut Roma 14:1-4 - Siahaya, Johannis; Rinukti, Nunuk; Setiawan, Ho Lucky; Siahaya, Charista Jasmine; Sutiono, Vicky Samuel (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
Harmony between the people of religion in Indonesia is not only the responsibility of the government, but it is also the responsibility of all Indonesians to maintain the integrity of the nation by building an attitude of tolerance and tolerance, and harmony among the people themselves. This also applies to Christians in Indonesia, to take part and be active in building harmony between religious communities. The Bible, especially Romans 14: 1-4 provides a good example for Christians to respect and respect one another, and not to humiliate and judge one another, so that inter-religious harmony can be maintained properly. And this is the model of religious moderation that Christian scriptures uphold. This research was written using a descriptive qualitative method using journal and book sources as the main reference. The discussion was carried out by explaining the concept of harmony of religious communities in Indonesia, then briefly describing the concept from a Christian perspective. The analysis, which is a deconstruction, is specifically directed at Romans 14: 1-4 which is in the spirit of harmony both internally and among religious communities within the framework of moderation in Indonesia. Opportunities and challenges according to Indonesian conditions are discussed at the end. The conclusion is that religious harmony according to Romans 14: 1-4, stimulates Christians to further increase religious moderation in Indonesia, which, although different in terms of ethnicity, ethnicity, religion, and RAS, is tolerant and accepts others as they are, makes it less difficult for Christians to judge and humiliate others.